Paradigm of the economic development of the agrarian and construction cluster under the conditions of war - Petrukha, S. (Ліра-К, 2022)
The theme of the extreme abstractness of the models of the comprehensive economic theory of the development of the agro-construction cluster, its excessive simplification and isolation from socio-economic reality, which occurs, in particular, during wartime, has been a key issue in the methodology of rural and construction economies for more than a decade.
Keywords: paradigm; economic development